Awareness on Rabies among People Receiving Rabies Vaccine in Kathmandu - Ale Magar, Sital; Poudel , Shrijana (NPRC Journal of Multidisciplinary Research, 2025)
Background: Rabies vaccine preventable viral disease which occurs in more than 150 countries and territories. Rabies virus is still prevailing worldwide in spite of many necessary measures to control and eradicate the disease. This research entitled “Awareness on Rabies among people receiving Rabies Vaccine in Kathmandu. Objective: The objective of the study was to assess awareness on Rabies among people receiving Rabies vaccine in Kathmandu. This study was conducted in OPD of Sukraraj Tropical and Infectious Disease Hospital (STIDH) at Teku, Kathmandu. Methods: A descriptive cross-sectional study design was used with non-probability purposive sampling technique The sample size was 104. Structured interview schedule was used for data collection. The obtained data was coded and analysed by using descriptive and inferential statistics. Findings: The finding of the study showed that only 14.4 percent had high level of awareness whereas 45.2 percent had low level of awareness. The study revealed that most of the respondents had heard about rabies. The main source of information was book 46.2 percent. Only 32.7 percent of the respondents mentioned that rabies is a highly fatal viral infection. Likewise, fear of water, air and light was most common sign and symptoms mentioned by (68.3) percent of the respondent. Majority (87.5%) of the respondents reported that rabies is a preventable disease. There was significant association between the level of awareness and previous history of bite (p